2015
DOI: 10.1007/s00431-015-2589-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the birth’s season on the development of celiac disease in Italy

Abstract: • This is the first study in Southern Europe to find a relationship between season of birth (summer) and development of CD. • Summer-born infants are introduced to complementary feeding (gluten) in winter, when the rotavirus infection is at its highest peak; this may be the link between season of birth and development of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The increased risk for celiac disease with spring and summer birth in various cohorts, albeit inconsistent,[37] was small in our two cohorts. Some of these previous studies have observed this association only in subsets of the studied population, calling for cautious interpretation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The increased risk for celiac disease with spring and summer birth in various cohorts, albeit inconsistent,[37] was small in our two cohorts. Some of these previous studies have observed this association only in subsets of the studied population, calling for cautious interpretation.…”
Section: Discussionmentioning
confidence: 59%
“…The recent increase in celiac disease indicates that yet unidentified environmental factors may play a role in its pathogenesis. [1, 2] Several studies found that celiac disease was more common in children born during spring or summer, [37] suggesting that environmental factors operating with seasonal fluctuations are involved. Although a potential link to low vitamin D in the perinatal period has been proposed,[4, 5] this hypothesis has not previously been tested.…”
Section: Introductionmentioning
confidence: 99%
“…A case–control study performed in Italy found the proportion of birth during the summer was significantly higher among cases of CD compared with healthy controls (odds ratio 1.315, 95% CI 1.100–1.572; ). The definition of seasons was also arbitrary: summer was from June to August and statistical analysis was not performed for the proportion of CD among total births, unlike the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the relationship between CD and seasonality of birth, but the evidence has not been clear. A study performed in three hospitals in Boston found that boys with CD tended to be born during the spring (11), while two studies performed in Sweden and Italy found that birth during the summer was associated with the development of CD (2,17,18). Another Swedish cohort study found that birth during the spring, summer and Abbreviations CD, Coeliac disease; CI, Confidence interval; HLA, Human leucocyte antigen; UV, Ultraviolet.…”
Section: Introductionmentioning
confidence: 99%
“…11 One study done in Italy has shown that children born in summer are at higher risk to develop CD than children born in other seasons. 14 In children within few months of introducing the child to wheat based foods, the classic syndrome of chronic diarrhea, abdominal distension and failure to thrive appears between 6 months and 2 years of age affecting their weight and growth. In some it remains undiagnosed until adulthood.…”
Section: Stagementioning
confidence: 99%